2010
DOI: 10.1093/cercor/bhq061
|View full text |Cite
|
Sign up to set email alerts
|

The Generation of Superficial Cortical Layers Is Regulated by Levels of the Transcription Factor Pax6

Abstract: The ventricular zone (VZ) of the embryonic dorsal telencephalon is a major site for generating cortical projection neurons. The transcription factor Pax6 is highly expressed in apical progenitors (APs) residing in the VZ from the earliest stages of corticogenesis. Previous studies mainly focused on Pax6(-/-) mice have implicated Pax6 in regulating cortical progenitor proliferation, neurogenesis, and formation of superficial cortical layers. We analyzed the developing cortex of PAX77 transgenic mice that overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 56 publications
7
58
3
Order By: Relevance
“…This observation directly supports our model that Ey/Toy control growth of the eye-antennal disc and is consistent with studies in vertebrates that demonstrate roles for Pax6 in the proliferation of neural progenitors within the brain (53,(78)(79)(80). Earlier studies observed cells undergoing apoptosis in Pax6 singlemutant eye-antennal discs and showed that blocking cell death alone can partially rescue the head defects of the ey D and toy hdl mutants (46).…”
Section: Discussionsupporting
confidence: 91%
“…This observation directly supports our model that Ey/Toy control growth of the eye-antennal disc and is consistent with studies in vertebrates that demonstrate roles for Pax6 in the proliferation of neural progenitors within the brain (53,(78)(79)(80). Earlier studies observed cells undergoing apoptosis in Pax6 singlemutant eye-antennal discs and showed that blocking cell death alone can partially rescue the head defects of the ey D and toy hdl mutants (46).…”
Section: Discussionsupporting
confidence: 91%
“…6A). These GFP signals colocalized with Cux1, which is known to be expressed in several cortical surface layers (II/III and IV after laminar organization) (71,72), but not with Tbr1, a marker of deep cortical layers (Fig. 6, B and C) (72,73 …”
Section: Thr-906 and Thr-1007 Mutation In Kcc2 Affects Activity And Smentioning
confidence: 92%
“…Our efforts to determine whether the length of the cell cycle is altered in the absence of Gde2 using a well-established paradigm involving spaced consecutive injections of IdU and BrdU showed no differences in cell-cycle length between Gde2 -/-and WT animals (M.R., J.C., S.P. and S.S., unpublished observations) (Georgala et al, 2011). A caveat of this approach is that it assumes that all progenitors share uniform cell-cycle parameters, which might not be the case in Gde2 -/-cortices given the changes in cellcycle exit in these animals that are superimposed on normal variations of cell-cycle length over time.…”
Section: Gde2 and The Temporal Control Of Cortical Neurogenesismentioning
confidence: 94%